Quality Management for Competitive Advantage in Global Markets - Saiz-Alvarez, J (IGI Global, 2020)
Quality should be treated as a culture of success in the market. Enterprises focused on quality will survive in the long term in this new environment because quality is what may create a real and robust link between a company and its clients, and these clients should always be considered the heart of any business; without them, there is neither option nor sense to continue any activity in a company. Quality Management for Competitive Advantage in Global Markets is an essential reference source that discusses the importance of quality practices and global market practices. With research that allows practitioners to improve their understanding of the strategic role of quality in the information and knowledge society, it focuses on describing a global economy formed by networks, organizations, teams, workgroups, information systems, and finally, actors in networked environments. Featuring research on topics such as consumer satisfaction, human capital, and quality management, the target audience of this book is composed of professionals and researchers working in the field of information and knowledge management in various disciplines including library, information and communication sciences, administrative sciences and management, education, adult education, sociology, computer science, and information technology. Moreover, the book provides insights and supports executives concerned with the management of expertise, knowledge, information, and organizational development in different types of work communities and environments. © 2021 by IGI Global. All rights reserved.